Mini Research Teknologi Keuangan Syariah Identitas Digital Vs Kejahatan Siber (Studi Intensitas Kasus dan Pola Kejahatan Siber Melalui Platform Digital) - Oktafiani, Rizka; Trisnawati, Shela Enindra; Maymunah, Siti; Paridah, Siti (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze digital identity and cybercrime patterns on various digital platforms. A digital identity is a digital version of a physical identity document as well as a credential that allows a person to access online services. Cybercrime is an unlawful act committed by someone with a computer network. The method used is Descriptive Qualitative research with a Statute Approach approach through legal rules in the implementation and supervision regulated in the Legislation. While the data used are secondary data obtained from library materials, books, research literature, previous research, and internet media. The result of this study is that it can find out the number of cyber cases in the form of phishing crimes that occurred in the 2018-2021 period. This crime case peaked in 2021 due to: 1) The number of new users who understand technology so that a new identity has emerged in the use of internet media. 2) The development of mass media on several platforms with all its advantages makes thinking in the mass media less and even not balanced with the rise of cybercrime.